Joint Income-Wealth Inequality: An Application Using Administrative Tax Data - David Gallusser; Matthias Krapf (Center for Economic Studies and ifo Institute (CESifo), 2019)
Using tax data from the Swiss canton of Lucerne, we study how measures of economic inequality change if they account for income and wealth rather than income alone. The joint distribution of income and wealth displays strong tail dependence at the top and a negative association for negative net wealth. Joint income-wealth, the sum of labor income and annuitized wealth, serves as a measure of combined inequality of income and wealth. Inequality measured using joint income-wealth is higher than measured using income alone. We refine existing annuitization techniques by introducing heterogeneous returns. A decomposition shows that the underlying marginal distributions of labor income and annuitized wealth account for most of joint income-wealth inequality, whereas their association matters only in the tails.
Keywords: 330